Excessive Prenatal Supplementation of Iodine and Fetal Goiter: Report of Two Cases Using Three-dimensional Ultrasound and Magnetic Resonance Imaging - Castro, Pedro; Werner, Heron; Marinho, Paulo Roberto Silva; Matos, Ana Paula; Pires, Pedro; Araujo Júnior, Edward (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Fetal thyroid complications in pregnancy are uncommon, and are commonly related to the passage of substances through the placenta. The excessive iodine intake during the pregnancy is a well-known mechanism of fetal thyroid enlargement or goiter, and invasive procedures have been proposed for the treatment of fetal thyroid pathologies. In the present report, we demonstrate two cases from different centers of prenatal diagnosis of fetal thyroid enlargement and/or goiter in three fetuses (one pair of twins, wherein both fetuses were affected, and one singleton pregnancy). The anamnesis revealed the ingestion of iodine by the patients, prescribed from inadequate vitamin supplementation. In both cases, the cessation of iodine supplement intake resulted in a marked reduction of the volume of the fetal thyroid glands, demonstrating that conservative treatment may be an option in those cases. Also, clinicians must be aware that patients may be exposed to harmful dosages or substances during pregnancy.
Keywords: fetal goiter; prenatal care; iodine supplementation; three-dimensional ultrasound; magnetic resonance imaging